Body Shape Questionnaire (BSQ) in young university Metropolitan Lima: Initial Evidence of Validity and Reliability - Palomino-Floriano, Alejandra (2023)
In order to evaluate the presence of corporal dissatisfaction in young men, it is important to have adequate instruments to measure this dissatisfaction and guarantee valid results. However, in Peru and several countries, there is not a great variety of appropriate tools to assess body image dissatisfaction. The present research aimed to adapt the Body Shape Questionnaire (BSQ) to a group of young male university students (N = 320) from Metropolitan Lima with an age range of 18 to 30 years. Results showed a 2-factor structure that explained 50.72% of the total variance. An excellent internal consistency was obtained in both factors: 1) Normative Body Uncomfort (α = .88) and 2) Pathological Body Uncomfort (α = .87). Regarding convergent and divergent validity, the BSQ showed good ability to determine the presence of body image dissatisfaction, denoting a positive and significant convergence between both BSQ factors with the PANAS Negative Affect, explaining how all these negative feelings are present and influence with this discomfort. Finally, the limitations and recommendations of the study, as well as the direction of future research are discussed.